Rosiglitazone fails to improve hypertriglyceridemia and glucose tolerance in CD36-deficient BN.SHR4 congenic rat strain - Seda, Ondrej; Kazdova, Ludmila; Krenova, Drahomira; Kren, Vladimir (Physiological genomics, 2003)
The favorable metabolic effects of thiazolidinediones are supposedly related to the peroxisome proliferator-activated receptor-gamma (PPARgamma)-driven changes in lipid metabolism, particularly in free fatty acid (FFA) trafficking. The fatty acid translocase CD36 is one of the proposed PPARgamma targets to mediate this action. We assessed the effect of rosiglitazone (RSG, Avandia) administration in two inbred rat strains, BN/Cub and BN.SHR4 congenic strain, differing in 10 cM proximal segment of chromosome 4. Rats were fed high-sucrose diet with or without RSG for 1 wk. In BN.SHR4, which carries defective Cd36 allele of SHR origin, RSG failed to improve glucose tolerance (assessed by the oral glucose tolerance test), did not lower triglyceridemia, nor induced increases in epididymal and retroperitoneal adipose tissue weights and adipose tissue glucose utilization, effects observed in BN/Cub. On the other hand, the RSG-treated BN.SHR4 showed lower concentrations of FFA and substantial increase in glycogen synthesis and glucose oxidation in skeletal muscle. Altogether, these results support involvement of CD36 in RSG action, suggesting this pharmacogenetic interaction may be of particular importance in CD36-deficient humans.
Keywords: antigeny CD36; Animals; konzumní sacharóza; glukózový toleranční test; potkani inbrední BN; CD36 Antigens; porucha glukózové tolerance; Thiazoles; Thiazolidinediones; thiazoly; Glucose Tolerance Test; Adipocytes; Hypoglycemic Agents; Rats, Inbred BN; rosiglitazon; Insulin; Dietary Sucrose; Rosiglitazone; thiazolidindiony; dieta; hypoglykemika; Diet; Male; složení těla; aplikace orální; Glucose Intolerance; krysa rodu Rattus; Body Composition; Hypertriglyceridemia; potkani inbrední SHR; Administration, Oral; zvířata; tuková tkáň; mužské pohlaví; Adipose Tissue; inzulin; Rats; Rats, Inbred SHR; hypertriglyceridemie; tukové buňky